1989
DOI: 10.1507/endocrj1954.36.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromedin B on Insulin and Glucagon Release from the Isolated Perfused Rat Pancreas.

Abstract: The effect of neuromedin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, we did not find Nmb to be expressed outside the islets as evaluated using Nmb LacZ reporter mice. Second, we used a physiological range of exogenous NMB in the current study (0.1-100nM) whereas the stimulatory effect in rat pancreas was observed with 10mM NMB [21] but not with 10nM-1M NMB 32 Thus, although we cannot rule out species differences in responses to NMB, our studies using mouse and human isolated islets convincingly show that NMB is not an insulinreleasing peptide in both mice and humans. It is therefore evident that the conclusions drawn from obesity GWAS association studies on NMB, as well as on insulin release, should be taken with caution until additional independent studies confirm or refute our findings.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, we did not find Nmb to be expressed outside the islets as evaluated using Nmb LacZ reporter mice. Second, we used a physiological range of exogenous NMB in the current study (0.1-100nM) whereas the stimulatory effect in rat pancreas was observed with 10mM NMB [21] but not with 10nM-1M NMB 32 Thus, although we cannot rule out species differences in responses to NMB, our studies using mouse and human isolated islets convincingly show that NMB is not an insulinreleasing peptide in both mice and humans. It is therefore evident that the conclusions drawn from obesity GWAS association studies on NMB, as well as on insulin release, should be taken with caution until additional independent studies confirm or refute our findings.…”
Section: Discussionmentioning
confidence: 66%
“…In the same experiments, as a control the Gq-coupled receptor agonist carbachol (Cch) caused the expected significant potentiation of glucose-stimulated insulin secretion (Figure 4C). We finally investigated whether there might be species-specific differences, given that previous studies have shown insulin secretion from NMB perfused canine [22], but no effects in NMB treated rat pancreas 32 . Similar to the data obtained with mouse islets, increasing concentrations of NMB did not significantly affect basal or glucose-stimulated insulin secretion from isolated human islets, while the positive control Cch exhibited a significant stimulatory effect (Figure 4D).…”
Section: Nmb Supplementation Does Not Affect Glucose Metabolism Nor Stimulate Insulin Release From Mouse and Human Isletsmentioning
confidence: 99%
“…4 C). We finally investigated whether there might be species-specific differences, given that previous studies have shown insulin secretion from NMB perfused canine 22 , but no effects in NMB treated rat pancreas 32 . Similar to the data obtained with mouse islets, increasing concentrations of NMB did not significantly affect basal or glucose-stimulated insulin secretion from isolated human islets, while the positive control Cch exhibited a significant stimulatory effect (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrin-releasing peptide Innervation (98) Murine islets (129) and INS-1 cells (130) Effects on endocrine secretion of rat islets (129) Ghrelin Rat islets (131,132) Rat islets (132) Effects on endocrine secretion of rat islets (133,134) and beta cells (135) Growth hormone-releasing hormone Rat islets (136) Effects on endocrine secretion of rat islets (137) Guanylin Beta cells of rat islets show uroguanylin immunoreactivity (138) Kisspeptin Murine and human islets (139) Effects on endocrine secretion of rat islets (140) Murine and human islets (139) Leptin Rat beta cells (141) Effects on endocrine secretion of rat beta cells (142,143) Luteinising hormone-releasing hormone Rat islets (144) Effects on endocrine secretion of rat islets (145) Melanin-concentrating hormone Expressed in murine and human islets and the betaTC3 cell line (146) MCHR1 is expressed in rat islets (147) and in murine and human islets and the betaTC3 cell line (146) Effects on endocrine secretion of rat islets, (147) regulation of beta cell mass (146) Neuromedin B Effects on endocrine secretion of rat islets (148,149) Neuromedin C Effects on endocrine secretion of rat islets (149) Neuromedin U Rat islets (150) Effects on endocrine secretion of rat islets (150) Neuropeptide Y Rat islets, (151) foetal mice, (152) innervation (98) Y1 receptor in rat islets (153) Effects on endocrine secretion of rat islets, (154) beta cell replication …”
Section: Receptor Localisation Bioactivitymentioning
confidence: 99%
“…Expressed in murine and human islets and the betaTC3 cell line (146) MCHR1 is expressed in rat islets (147) and in murine and human islets and the betaTC3 cell line (146) Effects on endocrine secretion of rat islets, (147) regulation of beta cell mass (146) Neuromedin B Effects on endocrine secretion of rat islets (148,149) Neuromedin C Effects on endocrine secretion of rat islets (149) Neuromedin U Rat islets (150) Effects on endocrine secretion of rat islets (150)…”
Section: Melanin-concentrating Hormonementioning
confidence: 99%